Proposed Digital Marketing Strategy with Product and Customer Service Improvement to Increase Consumers’ Intention to Use PosGiro Mobile (The Indonesian Journal of Business Administration, 2021)
PT Pos Indonesia is the state-owned company which is responsible to provide postal and financial service in Indonesia. Recently PT Pos developed product service called PosGiro Mobile (PGM). However, PT Pos has difficulties to catch up with the rapidly changing business environment particularly in providing user friendly financial service to its consumer, as such they hardly adopt the product and have confusion on the usage of PGM apps. Accordingly, the purpose of this study is: (1) to identify factors that significantly influence consumer intention to use digital financial service. (2) to determine the role of the significant factors in increasing consumer intention to use digital financial service. (3) to propose the right strategy to increase the intention to use PosGiro Mobile financial service.This study used mix method of qualitative and quantitative research to asses external and internal environments of PGM. First, general environment analysis, industry analysis, and competitor analysis were conducted to assess external environment of PT Pos. Second, it is analyzed the internal company situation using marketing mix, STP, and VRIO analysis approaches. And third, it is conducted a quantitative survey to gain consumer insights on factors that may increase the intention to adopt digital financial services using Technology Acceptance Model approach. The overall result of analysis then summarized in SWOT Analysis; and also becomes the input to identify the root causes problem of the business issue. As the result, it found eight root causes of PosGiro Mobile low adoption, Then, it is formulated 12 alternative solutions based on TOWS matrix approach and the relevant alternatives are connected with the root causes of problem are used to develop digital marketing strategies, which consists of online content marketing, online display advertising, PGM apps features improvement, and social media marketing strategies. Keywords: Digital Marketing, Technology Acceptance Model, Fintech